A versatile enrichment of functionalized calixarene as a facile sensor for amino acids. (28th January 2022) - Parikh, Jaymin; Bhatt, Keyur; Modi, Krunal; Patel, Nihal; Desai, Ajay; Kumar, Sandeep; Mohan, Brij
Abstract: Amino acids are the most important part of the human biological system due to their role in living processes. The role of amino acids stretches beyond their traditional role as a building block for proteins, and deficiency of amino acids could lead to decreased immunity, digestive problems, depression, fertility issues, lower mental alertness, slowed growth in children, and many other health issues. The acute detection of amino acids is necessary to determine the human health domain. Here, in this review, we summarize and study the calixarenes as complexes that are of immeasurable value and their utilization for amino acid detection. Key factors such as noncovalent forces, limit of detection, and the supramolecular chemistry of calixarenes with amino acids have been well described. This study presents the most recent efforts made towards the development of potential and highly efficient calixarene‐based sensors for the detection of amino acids. Abstract : Calixarene‐based macrocycles selectively form a host–guest complex with a range of analytes (amino acids) via various noncovalent interactions, which results in an obvious change in its fluorescence properties, making it an efficient selective and sensitive sensor for the detection of amino acids. These sensors can detect amino acids even at very low concentrations, and its selectivity is unaffected even in the presence of other interfering amino acids. This property of calixarene makes it a very exciting macrocycle to explore for its application as a real‐time sensor of amino acids.